Nickel abundance in stony cosmic spherules: Constraining precursor material and formation mechanisms - Cordier, Carole; van Ginneken, Matthias; Folco, Luigi (Meteoritics & Planetary Science, 2011)
We report bulk and olivine compositions in 66 stony cosmic spherules (Na2O < 0.76 wt%), 200–800 μm in size, from the Transantarctic Mountains, Antarctica. In porphyritic cosmic spherules, relict olivines that survived atmospheric entry heating are always Ni‐poor and similar in composition to the olivines in carbonaceous or unequilibrated ordinary chondrites (18 spherules), and equilibrated ordinary chondrites (one spherule). This is consistent with selective survival of high temperature, Mg‐rich olivines during atmospheric entry. Olivines that crystallized from the melts produced during atmospheric entry have NiO contents that increase with increasing NiO in the bulk spherule, and that range from values similar to those observed in chondritic olivines (NiO generally <0.5 wt%) to values characteristic of olivines in meteoritic ablation spheres (NiO > 2 wt%). Thus, NiO content in olivine cannot be used alone to distinguish meteoritic ablation spheres from cosmic spherules, and the volatile element contents have to be considered. We propose that the variation in NiO contents in cosmic spherules and their olivines is the result of variable content of Fe, Ni metal in the precursor. NiO contents in olivines and in cosmic spherules can thus be used to discuss their parent body. Ni‐poor spherules can be derived from C‐rich and/or metal‐poor precursors, either related to CM, CI, CR chondrites or to chondritic fragments dominated by silicates, regardless of the parent body. Ni‐rich spherules (NiO > 0.7 wt%) that represent 55% of the 47 barred‐olivine spherules we studied, were derived from the melting of C‐poor, metal‐rich precursors, compatible with ordinary chondrite or CO, CV, CK carbonaceous chondrite parentages.